The Russian Revolutionary Emigres, 1825-1870 - Miller, Martin A. (Johns Hopkins University Press, 2019)
Originally published in 1986. Martin A. Miller, author of the definitive biography of the exiled revolutionary Peter Kropotkin, traces the history of the first generations of Russians who went to Western Europe to devote their lives to anti-tsarist politics. Refusing to assimilate abroad and unable to return home, the émigrés political orientations were influenced by intellectual and social currents in both Russia and Europe. Miller undertakes a major reassessment of the émigré contribution to the Russian revolutionary movement. Starting with Nikolai Turgenev, who in 1825 was declared the first "émigré" by a special act of the Russian government, the exiles formed a unique social and political group. Miller takes a biographical approach in tracing the progression from a disparate community of intellectuals, unable to act together to promote their own program for change, to a more cohesive second émigré generation that provided the foundation for collective action and the development of a revolutionary ideology. The creation of the Russian émigré press, Miller argues, gave identity and momentum to the émigrés and helped promote their program of revolution and a new social order. The Russian Revolutionary Emigres, 1825-1870 concludes with the death in 1870 of the leading émigré figure, Alexander Herzen, and with an analysis of the impact upon the émigrés of the emergence of the populist revolutionary movement within Russia. The émigrés overcame the loss of their homeland through their version of a future Russia, one transformed into a new society where their ideals could be realized. When, two generations later, Lenin returned to Russia after decades in Europe and made this vision a reality, his actions built on the foundation laid by his nineteenth-century predecessors.